Does identity affect aspirations in rural India? An examination from the lens of caste and gender - Alvi, Muzna; Ward, Patrick S.; Makhija, Simrin; Spielman, David J. (International Food Policy Research Institute, 2019)
We use priming, a concept popular in social psychology, to study the effect of identity salience on aspirations for self and children as part of an impact evaluation in Odisha, India. We measure the effect of an individual’s genderand caste-identity salience on improving aspirations for themselves and for their children’s future profession and education. We find that when women are primed on gender, they exhibit higher aspirations for their daughters. Similarly, low-caste women primed on caste are more aspirational for their daughters. We do not find similar results for men. The effect of caste priming is more apparent in areas where significant ethnic heterogeneity exists and muted in ethnically homogenous areas. We find that aspirations for boys are already very high, thus priming has no effect on aspirations for sons.